Influence of exterior infill walls on the performance of RC frames under tsunami loads: Case study of school buildings in Sri Lanka. (1st May 2021) - Del Zoppo, Marta; Wijesundara, Kushan; Rossetto, Tiziana; Dias, Priyan; Baiguera, Marco; Di Ludovico, Marco; Thamboo, Julian; Prota, Andrea
Highlights: In-plane and out-of-plane performance of exterior infill walls is considered during the tsunami assessment. Shear failures cannot be properly detected if the progressive out-of-plane failure of infill walls is neglected. The Froude number strongly affects the performance of structural and non-structural components. The adoption of non-breakaway infill walls consistently leads to premature structural failure mechanisms. Abstract: This paper assesses the structural performance of RC frame buildings subjected to tsunami-induced loads, accounting for the influence of exterior masonry infill walls on the overall structural performance. Both the in-plane and out-of-plane contributions of masonry infill walls are considered in the analysis. To illustrate the importance of accounting for exterior infill walls in the response of structures to tsunami, two case study buildings are considered and modelled in 3D. The first case study is a typical two-storey school building in Sri Lanka, and the second is a modified version of this design configuration proposed in Sri Lanka after the 2004 Indian Ocean Tsunami to provide more redundancy against scour. Through these case studies, the effect of the non-uniform distribution of infill walls in the building and their failure (or "breakaway") on building performance is considered. The building performance is characterized by a number of response parameters (i.e., first yielding, development of two hinges, and shear failure in ground floor columns). The paper shows that the in-plane behaviour of exterior infill walls increases the flexural capacity and lateral stiffness of the structure, as would be expected. However, it also shows that an assumption of non-breakaway infill walls consistently leads to premature structural failure mechanisms, associated with the concentration of drag forces on seaward columns only. The results demonstrate that a good estimation of the location and occurrence of shear failure in structural elements can only be achieved by explicitly considering the out-of-plane behaviour and failure of exterior infill walls during an incremental tsunami load analysis. Finally, the Froude number assumed for the analysis is seen to strongly affect the performance of both structural and non-structural components, highlighting the importance of choosing realistic tsunami properties to perform a reliable capacity assessment.